A study into guest perceptions of service quality and loyalty in hotels in Harare - Mangwiro, Marvellous; Marimo, Rejoice Martha; Ndlovu, Agatha Olga (Exclusive journal publishing house, 2016)
This study was aimed at establishing the perceptions of guests towards service delivery in selected hotel restaurants and to ascertain loyalty levels among guests in hotel restaurants. Qualitative methodologies were used to establish customer perceptions of service quality and loyalty in selected hotel restaurants in Harare. Semi-structured interviews were conducted with 27 guests. Using thematic analysis, four themes emerged as guests‟ most important attributes for evaluating service experiences. These are customer service and attitude of service personnel, cleanliness of staff and of the physical environment, price and food quality. From the study, it can be concluded that the features of a restaurant establishment are not equally important to guest when evaluating their restaurant experience but rather the product itself and how it is delivered. It can is recommended that hotel restaurants in order to improve guests‟ perceptions of service experience and loyalty, need to motivate and empower customer contact employees so that a smooth service is delivered to the guests. Further studies should be done in the form of a comparative study using qualitative and quantitative methodologies to see if they can arrive at the same conclusion.